Creation of effective antireflux mechanism without creation of submucosal tunnel in surgical correction of vesicoureteric reflux: Myth or reality?-An experimental study - Archika Gupta; Shiv Narain Kureel (Wolters Kluwer Medknow Publications, 2014)
Objective: To evaluate the possibility of creating an effective antireflux mechanism without the need to create submucosal tunnel in surgical correction of vesicoureteric reflux. Materials and Methods: Ethical clearance was obtained from the institute ethical committee. The prospective experimental study was conducted on fresh postmortem specimens comprising of intact ureter-bladder-urethra of slaughtered lamb. Through perurethral tube, bladder distension revealed intact antireflux mechanism which disappeared following a cephalad slit of ureteric orifice. After intravesical advancement, mobilized ureters were anchored to the hiatus and the exposed detrusor along the proposed submucosal tunnel after stripping the bladder mucosa. Limited nonobstructed narrowing of the advanced ureteric ends was fashioned. After closure, bladder was distended and reflux was observed through proximal transected ureteric orifices with check cystogram. In second part of experiment, in a rectal reservoir, two intestinal segments as dilated ureters were implanted without creating submucosal tunnel, but anchoring the intrarectal segment to exposed submucosa. Intraluminal end of one segment was narrowed, while other left as such. Reservoir distension test was done to notice the status of reflux. In 24 months, 12 experiments were conducted. Results: In first part of experiment, successful antireflux mechanism was created in 11 ureters. In second part of experiment, reflux persisted in the ureteral segment implanted with obliquity but without distal nonobstructed narrowing, while there was no reflux in the ureteral segment with both obliquity and narrowing. Conclusion: Advancement and anchoring of the ureteral segment to the exposed detrusor with creation of nonobstructive and limited narrowing can create effective antireflux mechanism without the need to create submucosal tunnel.